Pengembangan Pembelajaran Inklusif Berbasis Problem-Based Learning untuk Meningkatkan Keterampilan Berpikir Kritis dan Sikap Ilmiah Siswa di Wilayah 3T Provinsi Riau - Azhar; Talia Ananda; Daeng Ayub; Dedi Irawan (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to develop an inclusive learning model based on Problem-Based Learning (PBL) to enhance students’ critical thinking skills and scientific attitudes in the 3T regions (frontier, outermost, and disadvantaged areas) of Riau Province, Indonesia. The research is motivated by the limited access to quality education in 3T areas, which affects students’ higher-order thinking skills and mastery of scientific attitudes. The model was developed using a Research and Development (R&D) approach adapted from the Borg & Gall framework, involving preliminary studies, model design, expert validation, revision, and limited trials. The research subjects were high school students in one of the 3T schools. Instruments used included a critical thinking skills test, a scientific attitude questionnaire, observation sheets, and interview guidelines. The results show that the inclusive PBL model developed is valid, practical, and effective for classroom implementation. Its application successfully improved students’ critical thinking skills through contextual problem-solving activities and fostered scientific attitudes such as curiosity, openness to evidence, and responsibility in the learning process. This study recommends the inclusive PBL model as an alternative instructional strategy for schools in 3T areas to support equitable improvement in education quality.